Functional Outcome of Human Adipose Stem Cell Injections in Rat Anal Sphincter Acute Injury Model. (31st January 2018) - Kuismanen, Kirsi; Juntunen, Miia; Narra Girish, Nathaniel; Tuominen, Heikki; Huhtala, Heini; Nieminen, Kari; Hyttinen, Jari; Miettinen, Susanna
Abstract : Anal incontinence is a devastating condition that significantly reduces the quality of life. Our aim was to evaluate the effect of human adipose stem cell (hASC) injections in a rat model for anal sphincter injury, which is the main cause of anal incontinence in humans. Furthermore, we tested if the efficacy of hASCs could be improved by combining them with polyacrylamide hydrogel carrier, Bulkamid. Human ASCs derived from a female donor were culture expanded in DMEM/F12 supplemented with human platelet lysate. Female virgin Sprague-Dawley rats were randomized into four groups (n = 14–15/group): hASCs in saline or Bulkamid (3 × 10 5 /60 μl) and saline or Bulkamid without cells. Anorectal manometry (ARM) was performed before anal sphincter injury, at two (n = 58) and at four weeks after (n = 33). Additionally, the anal sphincter tissue was examined by micro-computed tomography (μCT) and the histological parameters were compared between the groups. The median resting and peak pressure during spontaneous contraction measured by ARM were significantly higher in hASC treatment groups compared with the control groups without hASCs. There was no statistical difference in functional results between the hASC-carrier groups (saline vs. Bulkamid). No difference was detected in the sphincter muscle continuation between the groups in the histology and μCT analysis. More inflammation was discovered in the group receiving saline with hASC. The hASC injection therapy with both saline and Bulkamid is a promising nonsurgical treatment for acute anal sphincter injury. Traditional histology combined with the 3D μCT image data lends greater confidence in assessing muscle healing and continuity.